A Potential Role for Excess Tissue Iron in Development of Cardiovascular Delayed Effects of Acute Radiation Exposure. Issue 5 (November 2020) - Miller, Steven J.; Chittajallu, Supriya; Sampson, Carol; Fisher, Alexa; Unthank, Joseph L.; Orschell, Christie M.
Abstract : Abstract: Murine hematopoietic-acute radiation syndrome (H-ARS) survivors of total body radiation (TBI) have a significant loss of heart vessel endothelial cells, along with increased tissue iron, as early as 4 mo post-TBI. The goal of the current study was to determine the possible role for excess tissue iron in the loss of coronary artery endothelial cells. Experiments used the H-ARS mouse model with gamma radiation exposure of 853 cGy (LD50/30) and time points from 1 to 12 wk post-TBI. Serum iron was elevated at 1 wk post-TBI, peaked at 2 wk post-TBI, and returned to non-irradiated control values by 4 wk post-TBI. A similar trend was seen for transferrin saturation, and both results correlated inversely with red blood cell number. Perls' Prussian Blue staining, used to detect iron deposition in heart tissue sections, showed myocardial iron was present as early as 2 wk following irradiation. Pretreatment of mice with the iron chelator deferiprone decreased tissue iron but not serum iron at 2 wk. Coronary artery endothelial cell density was significantly decreased as early as 2 wk vs. non-irradiated controls (P<0.05), and the reduced density persisted to 12 wk after irradiation. Deferiprone treatment of irradiated mice prevented the decrease in endothelial cell density at 2 and 4 wk post-TBI compared to irradiated, non-treated mice (P<0.03). Taken together, the results suggest excess tissue iron contributes to endothelial cell loss early following TBI and may be a significant event impacting the development of delayed effects of acute radiation exposure.